2008
DOI: 10.1073/pnas.0803574105
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 is critical for lung tumorigenesis and bronchioalveolar stem cell expansion

Abstract: Understanding the pathways that control epithelial carcinogenesis is vital to the development of effective treatments. The Polycomb group family member Bmi1 is overexpressed in numerous epithelial tumors, but its role in their development has not been established. We now show a key role for Bmi1 in lung adenocarcinoma. Whereas lung development occurs normally in Bmi1-deficient mice, loss of Bmi1 decreases the number and progression of lung tumors at a very early point in an oncogenic K-ras-initiated mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 32 publications
6
165
0
Order By: Relevance
“…11,12 Bmi1 is also essential for cancer stem cells as demonstrated in a mouse leukemia model as well as in a mouse lung tumor model generated by the expression of a mutant K-ras gene in bronchioalveolar stem cells. 5,26 In addition, we previously demonstrated that forced expression of Bmi1 promotes the self-renewal of hepatic stem/progenitor cells and contributes to malignant transformation. 3 All these findings highlight the important role of Bmi1 in both the development and maintenance of cancer stem cell systems.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Bmi1 is also essential for cancer stem cells as demonstrated in a mouse leukemia model as well as in a mouse lung tumor model generated by the expression of a mutant K-ras gene in bronchioalveolar stem cells. 5,26 In addition, we previously demonstrated that forced expression of Bmi1 promotes the self-renewal of hepatic stem/progenitor cells and contributes to malignant transformation. 3 All these findings highlight the important role of Bmi1 in both the development and maintenance of cancer stem cell systems.…”
Section: Discussionmentioning
confidence: 99%
“…Polycomb group member Bmi1 is essential for the self-renewal and maintenance of BASCs and is, therefore, used as a BASC marker (Valk-Lingbeek et al, 2004;Dovey et al, 2008). Bmi1 is also known as a marker of various cancer cells (Bea et al, 2001;Vonlanthen et al, 2001;Dimri et al, 2002;Leung et al, 2004).…”
Section: Runx3 Is Essential For Bronchiolar Epithelial Cell Differentmentioning
confidence: 99%
“…K-ras mutation-independent lung adenoma development in Runx3 þ /À mice K-ras mutations are found in most chemically induced mouse lung adenomas (Dovey et al, 2008) and in about 40% of human AAHs (Westra et al, 1996). To determine whether the adenomas in Runx3 þ /À mouse lungs carried K-Ras mutations, we sequenced the K-ras gene in 10 spontaneous and 10 urethane-induced lung adenomas from Runx3 þ /À mice.…”
Section: Runx3 Is Essential For Bronchiolar Epithelial Cell Differentmentioning
confidence: 99%
See 2 more Smart Citations